Menafsir Luka Dan Kecantikan: Pendekatan Hermeneutika Dalam Novel Cantik Itu Luka Karya Eka Kurniawan - Isroyati; Yasir, Muhamad (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This study aims to reveal the symbolic meaning of “wounds” and “beauty” in the novel Cantik Itu Luka by Eka Kurniawan using Paul Ricoeur’s hermeneutic approach. This novel was chosen because it represents the experiences of Indonesian women in the context of colonial history, patriarchal power, and collective trauma through complex symbols. The method used is qualitative-descriptive research with tripartite hermeneutic analysis techniques: explanation, understanding, and appropriation. The results of the study show that the symbol of “beautiful” in the novel functions as a social construction that makes women’s bodies objects of power, while the symbol of “wounds” reflects personal trauma as well as collective wounds due to historical and social repression. Female characters such as Dewi Ayu and her children show the ambiguity between being victims and agents of resistance. Thus, Cantik Itu Luka not only offers a fictional story, but also becomes a reflection of the social, political, and cultural struggles that shape the identity of Indonesian women. This study emphasizes the importance of a hermeneutic approach in revealing the depth of meaning of literary texts as a representation of layered reality.